Odpowiedzi

2009-11-08T01:27:45+01:00
A)
5^12 - 1 = (5^6)^2 - 1 = (5^6 -1)*(5^6 +1) =
= [(5^3)^2 - 1]*(5^6 + 1) = (5^3 - 1)*(5^3 +1)*(5^6 = 1) =
= (125 - 1) *(5^3 +1)*( 5^6 + 1) =31*4*(5^3 + 1)*(5^6 + 1)

b)
3^18 - 2^18 = (3^9)^2 - (2^9)^2 =
= ( 3^9 - 2^9)*(3^9 + 2^9) =
= [(3^3)^3 -(2^3)^3]*(3^9 + 2^9) =
= [27^3 - 8^3]*(3^9 + 2^9) =
=(27 - 8)*(27^2 +27*8 + 8^2)*(3^9 + 2^9) =
= 19 *(27^2 + 27*8 + 8^2 )*(3^9 + 2^9)
1 1 1
2009-11-08T01:42:21+01:00
5^12 - 1 = (5^6)^2 - 1 = (5^6 -1)*(5^6 +1) = [(5^3)^2 - 1]*(5^6 + 1) = (5^3 - 1)*(5^3 +1)*(5^6 = 1) = (125 - 1) *(5^3 +1)*( 5^6 + 1) =31*4*(5^3 + 1)*(5^6 + 1)


3^18 - 2^18 = (3^9)^2 - (2^9)^2 = ( 3^9 - 2^9)*(3^9 + 2^9) =
= [(3^3)^3 -(2^3)^3]*(3^9 + 2^9) = [27^3 - 8^3]*(3^9 + 2^9) =(27 - 8)*(27^2 +27*8 + 8^2)*(3^9 + 2^9) = 19 *(27^2 + 27*8 + 8^2 )*(3^9 + 2^9)
3 2 3